Ace of Math - Mohd Radzi, Shanizan Herman; Ahmad Shanizan Imran Mohd Radzi, Puteri Azwa; Razak, Abdul Hadi Abdul (Universiti Utara Malaysia Press, 2018)
Ace of Math is a card game produced by implementing the combination of numbers and mathematical equations as to construct an expression of some particular numbers.This card game can be used as an alternative reference and tool to practice mathematical problems within the activities involved by implementing game-based learning. Ace of Math also helps to develop and sharpen the soft skills of the players when they are facing the challenges and opportunities generated by the game.FEATURES: One of the teaching and learning tools which blend education and entertainment is a card game. Ace of Math is an ideal teaching and learning tool as players able to develop and sharpen their basic mathematical skills actively, yet in a friendly and engaging environment.APPLICATION: Ace of Math is a competitive card game that uses the manipulation of numbers and math equations which are addition, subtraction, multiplication and division as to construct simple and complex math expression to complete certain objectives. The card game enables the players to compete with each other as to ful_llobjectives, such that in the end to become the winner. The implementation of game-based learning helps to motivate players to practice solving simple to complex math problem in a non-threatening and engaging environment. The card game helps to cultivate players’ potential in exploring the knowledge in math as well as their soft skills while completing the objectives of the game.The card game can be played from two to four players and suitable for 7 years of age and above through the engaging, non-threatening, playful, and competitive environment created by the card game itself. The biggest part of the gameplay requires the players to play the game which involve the elements of discussions, decision making and information.